[OP.5B.08] IMPACT OF SEASONALITY AND AIR POLLUTANTS ON CAROTID-FEMORAL PULSE WAVE VELOCITY IN HYPERTENSIVE PATIENTS. (September 2016) - Di Pilla, M.; Bruno, R.M.; Ghiadoni, L.; Stea, F.; Massetti, L.; Bertolozzi, I.; Taddei, S.; Modesti, P.A.
Abstract : Objective: The effects of seasonality on blood pressure (BP) and cardiovascular events are well established. However, the influence of seasonality and other environmental factors such as air pollutants on arterial stiffness, a key parameter for cardiovascular risk stratification in hypertensive patients, has never been analyzed. This cross-sectional study aimed at investigating whether seasonality (daily number of hours of light) and acute variations in outdoor temperature and air pollutants may affect carotid-femoral pulse wave velocity (PWV). Design and method: 731 hypertensive patients aged 30–88 years, 417 treated with antihypertensive drugs (241 men) seeking medical consultation in our outpatient clinics during a 5-year period (2006–2011) were enrolled. PWV and central BP values were measured noninvasively in a quiet, temperature-controlled (22–24°C) room. Data of the local office of the National Climatic Data Observatory were used to estimate meteorological conditions and air pollutants (PM10, O3, CO, N2O) exposure the same day of the vascular examination. Results: PWV (mean value 8.5 ± 1.8 m/s) was related to age (r = 0.467, p < 0.001), body mass index (BMI) (r = 0.132, p < 0.001), central systolic (r = 0.414, p < 0.001) and diastolic BP (r = 0.093, p = 0.013), daylight hours (r = −0.176, p < 0.001), mean outdoor temperature (r = −0.082, p = 0.027), O3 (r = −0.135, p < 0.001), CO (r = 0.096, p = 0.012), N2O (r = 0.087, p = 0.022) in the univariate analysis. Moreover PWV was higher in individuals with chronic kidney disease (CKD) (9.7 ± 2.4 vs 8.4 ± 1.7 m/s, p < 0.001), impaired fasting glucose (IFG)/diabetes mellitus (DM) (8.9 ± 1.9 m/s vs 8.4 ± 1.7, p < 0.001) and hypertriglyceridemia (8.7 ± 1.8 vs 8.4 ± 1.8 m/s, p = 0.04). In multiple linear regression analysis, adjusted for confounders, PWV was associated with daylight hours (β = −0.170; 95% CI: −0.273 to −0.067, p = 0.001). Daylight hours explained 1.2% of the variance of PWV in the overall population. Neither air pollutants concentration nor outdoor temperature remained significantly associated with PWV. The association between PWV and daylight hours was significant in untreated (p = 0.002) but not in treated patients (p = 0.08). Conclusions: Seasonality, expressed by the daily number of hours of light, independently affect PWV. The relationship is stronger in untreated patients. Thus, seasonality should be taken into account when assessing arterial stiffness for cardiovascular risk stratification or in clinical trials.